2016
DOI: 10.1007/s11661-016-3630-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thermomechanical Routes on the Distribution of Grain Boundary and Interface Plane Orientations in Transformed Microstructures

Abstract: In the current study, a series of thermomechanical routes were used to produce different microstructures (i.e., ferrite and martensite) in low-carbon low alloy steels. The five-parameter grain boundary character distribution was measured for all microstructures. The thermomechanical processing route altered the texture of the fully ferritic microstructure and significantly influenced the anisotropy of the grain boundary character distribution. Generally, the population of (111) planes increased with an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…[35,36] The manifestation of a relatively strong 001 h i texture evolved during deposition promotes the termination of planes with a (001) orientation. This is similar to other reports where cubic materials with strong {100}, [18] {101} [17] and {111} [37] texture, stimulate the plane orientation of (100), ( 101) and (111), respectively. The post-printing annealing treatment revealed a significant effect on the overall grain boundary plane distribution.…”
Section: Resultssupporting
confidence: 92%
“…[35,36] The manifestation of a relatively strong 001 h i texture evolved during deposition promotes the termination of planes with a (001) orientation. This is similar to other reports where cubic materials with strong {100}, [18] {101} [17] and {111} [37] texture, stimulate the plane orientation of (100), ( 101) and (111), respectively. The post-printing annealing treatment revealed a significant effect on the overall grain boundary plane distribution.…”
Section: Resultssupporting
confidence: 92%
“…The α/α-misorientation was mainly dominated by 60° boundaries at a high cooling rates. This was due to the fact that the formation of this boundary is most crystallographically favorable to minimize the transformation strain [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a number of studies have shown the effect of phase transformation paths [ 10 , 18 , 36 ], thermo- and thermomechanical processing [ 37 , 38 , 39 ], and chemical composition [ 40 ] on α/α grain boundary network characteristics (misorientation angle, plane orientation, population, connectivity) and on α precipitation mechanisms. Particularly, diffusion and shear are the two generally accepted phase transformation mechanisms in titanium alloys, which are usually controlled by varying the cooling rates from the single β-state [ 3 ] or (α + β)-field [ 41 ].…”
Section: Introductionmentioning
confidence: 99%